Answer:
The third expression: (2x)^3
Step-by-step explanation:
Plug in 3 for x in each expression
2x^3
2(3)^3
Use PEMDAS
2 (3 × 3 × 3)
2 (9 × 3)
2 (27)
54
2x^3 + 5
(The last expression told us 2x^3 = 54 so feel free to use this information to make life easier)
54 + 5
59
(2x)^3
(2 × 3)^3
Use PEMDAS
6^3
6 × 6 × 6
36 × 6
216
(x - 1)^3
(3 - 1)^3
Use PEMDAS
2^3
2 × 2 × 2
4 × 2
8
216 is the greatest value so the third expression is the answer
Answer:
There will be
billion messages sent or received in November.
Step-by-step explanation:
Given.
Number of text messages sent or received
billion.
Increment on the very next month ![=13\%=\frac{13}{100}=0.13](https://tex.z-dn.net/?f=%3D13%5C%25%3D%5Cfrac%7B13%7D%7B100%7D%3D0.13)
Lets find what is ![13\%\ of\ 215](https://tex.z-dn.net/?f=13%5C%25%5C%20of%5C%20215)
⇒![13\%\ of\ 215](https://tex.z-dn.net/?f=13%5C%25%5C%20of%5C%20215)
⇒![0.13\times 215=27.95](https://tex.z-dn.net/?f=0.13%5Ctimes%20215%3D27.95)
So we will add this value to our previous months data.
Now
Number of text messages sent in the month of November
billion.
Rounding to the nearest tenth the answer will be
billion.
So
billion text messages were sent or received in November.
Answer:
Given the equation: ![3x^2+10x+c =0](https://tex.z-dn.net/?f=3x%5E2%2B10x%2Bc%20%3D0)
A quadratic equation is in the form:
where a, b ,c are the coefficient and a≠0 then the solution is given by :
......[1]
On comparing with given equation we get;
a =3 , b = 10
then, substitute these in equation [1] to solve for c;
![x_{1,2} = \frac{-10\pm \sqrt{10^2-4\cdot 3 \cdot c}}{2 \cdot 3}](https://tex.z-dn.net/?f=x_%7B1%2C2%7D%20%3D%20%5Cfrac%7B-10%5Cpm%20%5Csqrt%7B10%5E2-4%5Ccdot%203%20%5Ccdot%20c%7D%7D%7B2%20%5Ccdot%203%7D)
Simplify:
![x_{1,2} = \frac{-10\pm \sqrt{100- 12c}}{6}](https://tex.z-dn.net/?f=x_%7B1%2C2%7D%20%3D%20%5Cfrac%7B-10%5Cpm%20%5Csqrt%7B100-%2012c%7D%7D%7B6%7D)
Also, it is given that the difference of two roots of the given equation is
i.e,
![x_1 -x_2 = \frac{14}{3}](https://tex.z-dn.net/?f=x_1%20-x_2%20%3D%20%5Cfrac%7B14%7D%7B3%7D)
Here,
, ......[2]
.....[3]
then;
![\frac{-10 + \sqrt{100- 12c}}{6} - (\frac{-10 + \sqrt{100- 12c}}{6}) = \frac{14}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-10%20%2B%20%5Csqrt%7B100-%2012c%7D%7D%7B6%7D%20-%20%28%5Cfrac%7B-10%20%2B%20%5Csqrt%7B100-%2012c%7D%7D%7B6%7D%29%20%3D%20%5Cfrac%7B14%7D%7B3%7D)
simplify:
![\frac{2 \sqrt{100- 12c} }{6} = \frac{14}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20%5Csqrt%7B100-%2012c%7D%20%7D%7B6%7D%20%3D%20%5Cfrac%7B14%7D%7B3%7D)
or
![\sqrt{100- 12c} = 14](https://tex.z-dn.net/?f=%5Csqrt%7B100-%2012c%7D%20%3D%2014)
Squaring both sides we get;
![100-12c = 196](https://tex.z-dn.net/?f=100-12c%20%3D%20196)
Subtract 100 from both sides, we get
![100-12c -100= 196-100](https://tex.z-dn.net/?f=100-12c%20-100%3D%20196-100)
Simplify:
-12c = -96
Divide both sides by -12 we get;
c = 8
Substitute the value of c in equation [2] and [3]; to solve ![x_1 , x_2](https://tex.z-dn.net/?f=x_1%20%2C%20x_2)
![x_1 = \frac{-10 + \sqrt{100- 12\cdot 8}}{6}](https://tex.z-dn.net/?f=x_1%20%3D%20%5Cfrac%7B-10%20%2B%20%5Csqrt%7B100-%2012%5Ccdot%208%7D%7D%7B6%7D)
or
or
![x_1 = \frac{-10 + \sqrt{4}}{6}](https://tex.z-dn.net/?f=x_1%20%3D%20%5Cfrac%7B-10%20%2B%20%5Csqrt%7B4%7D%7D%7B6%7D)
Simplify:
![x_1 = \frac{-4}{3}](https://tex.z-dn.net/?f=x_1%20%3D%20%5Cfrac%7B-4%7D%7B3%7D)
Now, to solve for
;
![x_2 = \frac{-10 - \sqrt{100- 12\cdot 8}}{6}](https://tex.z-dn.net/?f=x_2%20%3D%20%5Cfrac%7B-10%20-%20%5Csqrt%7B100-%2012%5Ccdot%208%7D%7D%7B6%7D)
or
or
![x_2 = \frac{-10 - \sqrt{4}}{6}](https://tex.z-dn.net/?f=x_2%20%3D%20%5Cfrac%7B-10%20-%20%5Csqrt%7B4%7D%7D%7B6%7D)
Simplify:
![x_2 = -2](https://tex.z-dn.net/?f=x_2%20%3D%20-2)
therefore, the solution for the given equation is:
and -2.
Answer:
x=-17.......................
Step-by-step explanation:
x+17=0